Position paper from the IBRA Symposium on Surgery of the Head - The 2nd International Symposium for Condylar Fracture Osteosynthesis, Marseille, France 2012 - Neff, Andreas; Chossegros, Cyrille; Blanc, Jean-Louis; Champsaur, Pierre; Cheynet, Francois; Devauchelle, Bernard; Eckelt, Uwe; Ferri, Joel; Real Gabrielli, Mario Francisco [UNESP]; Guyot, Laurent; Koppel, David Andrew; Meyer, Christophe; et al. (Churchill Livingstone, 2014)
Background: This is a position paper from the 2nd International Bone Research Association (IBRA) Symposium for Condylar Fracture Osteosynthesis 2012 was held at Marseille, succeeding the first congress in Strasbourg, France, in 2007. The goal of this IBRA symposium and this paper was to evaluate current trends and potential changes of treatment strategies for mandibular condylar fractures, which remain controversial over the past decades.Methods: Using a cross-sectional study design, we enrolled the consensus based on the panel of experts and participants in the IBRA Symposium 2012. The outcomes of interest were the panel and electronic votes on management of condylar base, neck and head fractures, and panel votes on endoscopic and paediatric condylar fractures. Appropriate descriptive and univariate statistics were used.Results: The consensus derived from 14 experts and 41 participant surgeons, using 12 case scenarios and 27 statements. The experts and participants had similar decision on the treatment of condylar base, neck and head fractures, as well as similar opinion on complications of condylar fracture osteosynthesis. They had a parallel agreement on using open reduction with internal fixation (ORIF) as treatment of choice for condylar base and neck fractures in adults. Endoscopic approaches should be considered for selected cases, such as condylar base fractures with lateral displacement. There was also a growing tendency to perform ORIF in condylar head fractures. The experts also agreed to treat children (> 12 years old) in the same way as adults and to consider open reduction in severely displaced and dislocated fractures even in younger children. Nevertheless, non-surgical treatment should be the first choice for children <6 years of age. The decision to perform surgery in children was based on factors influencing facial growth, appropriate age for ORIF, and disagreement to use resorbable materials in children.Conclusions: The experts and participating surgeons had comparable opinion on management of condylar fractures and complications of ORIF. Compared to the first Condylar Fracture Symposium 2007 in Strasbourg, ORIF may now be considered as the gold standard for both condylar base and neck fractures with displacement and dislocation. Although ORIF in condylar head fractures in adults and condylar fractures in children with mixed dentition is highly recommended, but this recommendation requires further investigations. (C) 2014 European Association for Cranio-Maxillo-Facial Surgery. Published by Elsevier Ltd. All rights reserved.
Keywords: Condylar fracture; Osteosynthesis; Paediatric fractures; Consensus; Position paper